RESPONS OF GROWTH ANALYSIS PARAMTERS OF SOME COTTON CULTIVARS TO INTEGRATED WEED MANAGEMENT - & Hammood, Al-Chalabi (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2016)
A field experiment was conducted at the experimental field, Department of Field Crop - College of  Agriculture Abu-Ghraib- University of Baghdad, during summer season at 2012 and 2013, to determine the response of  growth analysis parameters in some cotton cultivars to Integrated Weed Management. A randomized complete block design (RCBD) arranged according to split-plot was used with three replicates, included six weed control treatments as Main-plots where as Sub-plots included eight cotton cultivars. The results showed various to response of  growth analysis parameters to weed control treatments , the treatment of weedfree with normal crop density of 106667 plant.h-1 and high crop density of 200000 plant.h-1 during 70 -90 days after sowing achieved highest crop growth rate of 10.80 , 9.87 g.m-2.day-1 at first season respectively and 9.81, 9.35 g.m-2.day-1 at second season respectively, and highest net assimilation rate of 1.668 , 1.208 mg.cm-2.day-1 at first season respectively, and 1.504 , 1.004 mg.cm-2. day-1 at second season respectively, highest relative growth rate of  50.48 , 48.52 mg.g-1. day-1 at first season respectively, and 38.49 , 37.78 mg.g-1.day-1 at second  season respectively , Has cultivar in first season and Marsomi-1 cultivar in second season achieved  highest crop growth rate of 9.62 , 9.03 g.m-2.day-1 respectively, highest net assimilation rate of 1.399 ,1.188 mg.cm-2.day-1 respectively, Abu-Ghraib5 cultivar achieved highest relative growth rate of  57.19 , 44.66 mg.g-1.day-1 at both season respectively. The treatment of half rate of trifluraline 1.2 L.h-1 applied with high crop density with Has cultivar achieved  highest crop growth rate of  9.29 g.m-2.day-1 at first season, and with Marsomi-1 cultivar of  9.92 g.m-2. day-1 at second season, and highest net assimilation rate with Has cultivar of 1.163 , 1.040 mg.cm-2. day-1  at both season respectively, highest relative growth rate with Cocker 310 cultivar of  36.17 , 39.14 mg.g-1.day-1  at both season respectively, this results confirmed the integrated among cultivars, herbicides, and high crop density to improve this characters .